Fractional smelting by the means of calorific pump. - V. M. Miasoedenkov; G. A. Nosov; M. N. Razina (Тонкие химические технологии, 2007)
Feasibility study of the fractional smelting continuum process by the means of a calorific pump with a closed cycle on the working substance is provided in this article. It is shown that the usage of the calorific pump allows decreasing significantly power inputs for realization of the studied process.